The Implementation Of Digital Marketing Communication In Improving Products And Social C ommunity Of Dosroha Farmer Group - Simbolon, Besti Rohana; Simamora, Prietsawenny Riris T.; Panjaitan, Doli Tua Mulia Raja; Telaumbanua, Yogi Alfines; Waruwu, Sopannius (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
PKM with the title Application of Digital Marketing Communication in Improving Products and Social Community of Poktan Dosroha, delivered to farmers with low educational background, based on the number of those who did not attend school up to junior high school. Empowerment gived to them so that farmers understand digital marketing communication to introduce farmer groups and their products. Training is given to farmers aged 45 years and under on social community and utilization of social media. Second, Marketing Communication Training and the use of digital technology and website management for farmers aged 17-45 years so that they are able to utilize digital technology in terms of marketing agricultural production and utilizing land as little as possible for maximum production. Training on editing images, posters, videos through Adobe, Canva, Capcut applications for social media, as well as how to create advertisements and video advertisements. Application of Technology is creating social media accounts on TikTok and FB; creating videos with Adobe, Canva, Illustrator and Capcut applications; creating photos and advertisements for agricultural production so that they can be marketed. Some farmers have started making them on their personal TikTok, while farmer group videos are made on the TikTok of Poktan Dosroha. The service was welcomed by the village head and the head of the Dosroha farmer group and was also published on the Dosroha farmer group website which has been published. Kata Kunci: Communication; Marketing; Dosroha Farmer Group; Pagarjati